PROFESIONALISME GURU SD NEGERI SE-KECAMATAN WARUNGASEM KABUPATEN BATANG Suatu Tinjauan Aspek Persepsi Guru tentang Kepemimpinan Kepala Sekolah dan Motivasi Berprestasi Guru - Nugroho, Setyo (Universitas Muhammadiyah Surakarta, 2012)
The purposes of this study were: to analyze the influence of teacher perceptions of principal leadership to teacher profesionlisme, 2) to analyze the influence of achievement motivation to teacher, and 3) to analyze the influence of teacher perceptions of principal leadership and teacher achievement motivation teacher profesionlisme Elementary School District as Batang Warungasem. The quantitative approach is used in this research with population consists of all elementary school teachers as Warungasem Batang district with the status of civil servants, amounting to 190 people. The Sample are 148 people. Data collection method in this study is conducted through a questionnaire. The validity and reliability instrument have been test and that result is significant on 5%. The results showed that: 1) the teachersâ perceptions of principal leadership have a positive and significant effect to the teacher professionalism at 5%, 2) the teachers achievement motivation have a positive and significant efect to the teacher professionalism at 5% and 3) the teacher perceptions of principal leadership and teacher achievement motivation have a positive and significant effect on teacher professionalism elementary School District as Warungasem Batang at 5% significance level.